Sluices in the 'mud': Sluice construction in sixteenth-century Holland as testing ground for building on soft soils (Bulletin KNOB, 2024)
In the years 1540–1570, sluice construction in the Low Countries underwent an important transition. In addition to the introduction of mitre gates, the increasing use of stone was a vitally important innovation. The advantage of this building material was that it prolonged the lifespan of sluices and made it possible to build larger ones, with considerable benefits for shipping and water management. The improved sluices in turn contributed greatly to the rise and prosperity of the Dutch Republic. These new hydraulic works were much heavier than their wooden predecessors and needed to be securely anchored in the marshy clay and peat substratum. The structural aspects of sluice construction have been largely neglected to date. Sluice construction is regarded as a niche subject and as such cannot expect much attention from architectural historians. Unjustly so, because the construction of sluices did not evolve in a vacuum; it was a major task for municipal architects and contractors in the towns of the County of Holland. There are also indications that the structural challenges presented by building heavy stone sluices in the soft soils of Holland were crucial to the development of a scientific approach to building in peatland areas.Contemporary discussions about the best foundation engineering solutions for sluices shows that there were no standard solutions and that experts with a wide range of backgrounds were involved in their construction. We still have few details about the design of foundations in the sixteenth century and the extent to which the transition from wood to stone sluices contributed to the development of engineering solutions for improved foundations in general. Both experts and clients sought maximum certainty in an arena where knowledge was still evolving. Learning by example was essential and technical drawings and models became increasingly important tools for recording such acquired knowledge. A new, supra-regional knowledge network that included the southern Low Countries as well as Holland promoted the dissemination of new knowledge and expertise.The interconnection of sluice building with urban and church building projects means that rather than being a niche subject, the construction of stone sluices had wider implications. It provided a testing ground for building on soft soils whereby the exchange of knowledge, soil research, and concrete experiments during construction delivered vital knowledge and expertise for building in peat.